NEUTRON CAPTURE GAMMA RAY FIELD WITH ENERGY TO 10 MeV FOR METROLOGICAL SUPPORT OF RADIATION PROTECTION DEVICES - D. I. Komar; R. V. Lukashevich; V. D. Guzov; S. A. Kutsen (Приборы и методы измерений)
Medical, and technological linear particle accelerators, and nuclear reactors are vastly widespread worldwide today. These facility generate fields of secondary gamma radiation with energy to 10 MeV. Therefore, we have a need to calibrate spectrometric and dosimetric ionization measurement instruments for the energies to 10 MeV. The aim of this work is to determine possibility to use thermal neutron collimator of АТ140 Neutron Calibration Facility with 238Pu-Be fast neutron source (IBN-8-6) for this. Below 3 MeV we use a set of point gamma standard spectrometry sources OSGI. We can acquire gamma rays with energies above 3 MeV using radioactive thermal neutron capture on target, i.e. (n, γ)-nuclear reaction. We can use neutron capture gamma-ray from titanium target (to 7 MeV) or nickel target (to 10 MeV) situated in thermal neutron field for calibration. We can use thermal neutron collimator of АТ140 Neutron Calibration Facility with 238Pu-Be fast neutron source (IBN-8-6) for slowing down neutrons from radionuclide fast neutron sources to thermal energies in polyethylene. Thermal neutron collimator forms a beam from radionuclide source with a significant amount of neutrons with thermal energies. We placed Ti and Ni targets in collimator’s canal. We got experimental spectral data on detection unit BDKG-19M NaI(Tl) 63 × 160 mm with nonlinear channel-energy conversion characteristic in range to 10 MeV. For additional filtration we proposed to use polyethylene neutron reflector and lead discs. We experimentally determined that placement of lead discs in collimator in front of the target allows to filter all spectrum while insignificantly weakening target’s emission. Using theoretical and experimental data we proved the ability to calibrate gamma-ray spectrometers in the range to 10 MeV.